NNOVATIVE AND MARKETING TECHNOLOGIES AS TOOLS FOR GREENING RETAIL BUSINESS - O. V. Godina; L. S. Maksimenko; E. V. Tatasheva (Вестник Северо-Кавказского федерального университета, 2022)
The article discusses the problems of achieving sustainable development of retail business in the context of updating the environmental agenda and minimizing the negative impact on the environment. Innovative and marketing technologies are argued as alternative tools for increasing business activity and competitiveness of Russian retail. Their coupling from the positions ofperforming a reactive and proactive role of retail business in the greening of consumption allowed us to form a matrix of scenarios for choosing solutions to the problem of activating innovative processes and technological transformation of marketing for sustainable development. Practical testing on the materials of the ecobrand «Ekolavka» in Stavropol has shown that safety and sustainability are becoming so important for many customers, thet it is no longer worthy for retail to offer environmentally friendly products to make a positive impression on them - it is necessary to create new formats of relationships with consumers in which value is generated during the search, selection and after the purchase, turning the transaction into a unique consumer experience.